THE HEALTH OF YOUTH IN THE RUSSIAN SOCIETY: SOCIOLOGICAL ANALYSIS OF ADVERSE TENDENCIES - Gafiatulina, N H (History, Archeology and Ethnography of the Caucasus, 2016)
This article covers the main reasons of negative trends of health of the youth in the contemporary Russian society, including the social policy in the field of public health and health care, lack of education and training aimed to teach young people to be careful of their health, paradoxical attitude to the health.
Keywords: Russian youth; health; public health; Russian health care; determinants; healthy lifestyle; addictive behavior; social policy